Pengaruh Pemanfaatan Teknologi Informasi dan Motivasi Belajar terhadap Perilaku Belajar Siswa - Abdul Haris Abdullah (IAIN Manado, 2009)
This research aimed to describe: (1) the relationship between the utilization of Information Technology, learning motivation, and learning behavior; (2) the relationship of the utilization of Information Technology and learning motivation, individually or combined toward the learning behavior of the students of SMK in Manado City.The research sample was 84 students chosen proportionally from the total population of 530 students scattered at 4 SMK in Manado City. This research applied survey method with data collecting technique through questionnaires which had been tested before for their validity and reliability. Furthermore, the collected data was analyzed by computer, using SPSS 16 for Windows 2007.Based on the research analysis, the following findings were: (1) Relationship was found between the utilization of Information Technology, learning motivation, and learning behavior; (2) significant impact was found between the utilization of information technology and learning motivation toward learning behavior of the students of SMK in Manado City, either individually or combined.Kata Kunci: Information Technology, Motivation, Learning behaviour